Neuromuscular synergy characteristics of Tai Chi leg stirrup movements: optimal coordination patterns throughout various phases - Zhang, Xiaopei; Jia, Mengyao; Ke, Yong; Zhou, Jihe (Frontiers in Bioengineering and Biotechnology, 2024)
Objective To investigate the neuromuscular activity characteristics of Tai Chi athletes and identify optimal muscle synergy patterns. Method Data were collected from 12 elite Tai Chi athletes using a Vicon motion capture system, a Kistler 3D force plate, and a Noraxon surface electromyography system. Muscle synergy patterns were extracted using Non-negative Matrix Factorization. Results Four muscle synergy patterns were identified in each of the three phases of the leg stirrup movement, with the optimal synergy pattern for each phase determined as follows: knee lift phase: rectus femoris and vastus lateralis of the right leg; extension phase: rectus femoris, vastus lateralis, biceps femoris, and medial gastrocnemius of the right leg; recovery phase: rectus femoris, vastus lateralis, and medial gastrocnemius of the right leg. These patterns explain the muscle coordination activities for each phase. Conclusion This study identified the optimal muscle synergy patterns for each phase, supporting the fluidity and force generation of the leg stirrup movement. This provides Tai Chi athletes with a more efficient way to exert strength and maintain balance.